Draft Proposals Fourth Five Year Plan Haryana State Volume I (Memorandum and Summary Statements I, II & IV) - Planning Commission (Planning Commission, 1966)
The new state of Haryana, the 17th state of the Indian Union, formally came into existence on the 1st November, 1966. This state has a population of 76 1akhs and an area of about 16,951 square miles. The areas of the new Punjab state is only marginally higher, i.e., 19,430 square miles but its population is about 50% higher, i.e., 112 lakhs. The population of the two states is, thus, in the ratio of 40:60 or 2:3.
Government of Haryana Planning Department